Risk Factors and Severity Indicators of Female Pelvic Organ Prolapse: Insights from a Comprehensive Retrospective Study with a Large Sample Size - Qiao Li; Xiaoyu Niu; Yueyue Chen; Can Luo; Yueting Zhang; Jian Meng; Dongmei Wei (Clinical and Experimental Obstetrics & Gynecology)
Background: Pelvic organ prolapse (POP) is a common condition worldwide, predominantly affecting middle-aged and elderly postmenopausal women. However, its pathogenesis, etiology, and associated risk factors remain unclear. This study aimed to analyze the distribution of POP severity stages, identify associated risk factors, and explore its underlying pathogenesis to develop strategies for early prevention and intervention. Methods: This retrospective study included all patients diagnosed with POP using the pelvic organ prolapse quantification (POP-Q) system at the outpatient clinic of West China Second Hospital, Sichuan University, between January 2015 and January 2019. A univariate Chi-square test and multivariate logistic regression analysis were performed to evaluate the relationships between the identified factors. Results: Among 9569 patients with anterior vaginal wall prolapse, the severity was distributed as follows: grade I (38.52%), grade II (60.70%), grade III (0.77%), and grade IV (0.01%). Among the 9495 patients with posterior vaginal wall prolapse, the severity was distributed as follows: grade I (90.37%), grade II (9.47%), and grade III (0.16%). Among the 932 patients with uterine prolapse, the severity was distributed as follows: grade I (85.84%), grade II (5.36%), grade III (7.62%), and grade IV (1.18%). Multivariate logistic regression analysis identified several significant risk factors associated with the progression of anterior vaginal wall prolapse, including advanced maternal age (AMA) (≥35 years), body mass index (BMI) (≥25 kg/m2), parity (≥2), and vaginal delivery (p < 0.05). For posterior vaginal wall prolapse, significant risk factors included AMA (≥35 years), BMI (≥25 kg/m2), manual labor, and vaginal delivery (p < 0.001). Additionally, AMA (≥35 years) was identified as a significant risk factor for the progression of uterine prolapse (p < 0.05). Conclusions: Grade II prolapse was most commonly observed in the anterior vaginal wall, whereas grade I prolapse predominantly occurred in the posterior vaginal wall. Key risk factors for POP include childbearing age, parity, BMI, and mode of delivery, with AMA identified as independent risk factors. Vaginal delivery specifically increases the likelihood of vaginal prolapse, while occupations involving prolonged physical labor correlate with a higher incidence of posterior vaginal wall prolapse. Based on the identified risk factors, targeted prevention and intervention measures are recommended to facilitate early identification and reduce the incidence of POP.